Risk Factor Mild Mental Retardation in Extraordinary School at Surabaya - Muhammad Helmi Imaduddin; Nining Febriyana; Yunias Setiawati; Irwanto Irwanto (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Children with mild mental retardation tend to have late language skills so that it affects aspects of speech and independence and can persist into adulthood. Knowing the risk factor of mental retardation is important because disability in children can be prevented by knowing the cause. Objective: This study aims to analyze risk factors for students with mild mental retardation in special schools in Surabaya in the academic year 2019-2020. Methods: This study was an observational analytic study with a case-control approach that took primary data in the form of a questionnaire on parents. Then the data is analyzed through univariate to display the characteristics of respondents and descriptive research variables and bivariate analysis with a chi-square test to determine the effect of risk factors on mental retardation. Results: In this study, there was a total of 100 samples after being excluded from 192 samples. Factors obtained by the length of neonatal stay in the hospital (p=0.010, OR=0.318, 95%CI=0.131-0.775), baby cries immediately at birth (p=0,000, OR=0.052, 95%CI=0,007-0,417), antenatal care (p=0.014, OR=0.107, 95%,CI=0.013-0.889), LBW (p=0.002, OR=0.820, 95%CI=0,72000,934), prematurity (p=0,007, OR=0,148, 95%CI=0,031-0,706), family income (p=0,000, OR=0.077, 95%CI=0.028-0.207), father's education (p=0.001, OR=5.310, 95%CI =1,913 14,745) affect mild mental retardation. Conclusion: Factors that influence mild mental retardation consist of perinatal factors (baby crying at birth) and environmental factors (family income and father's education).